Regulation and Supervision of Food Irradiation - Mariana Alonso Natividade; Thessa Cristina Alonso; Amir Zacarias Mesquita (Brazilian Journal of Radiation Sciences, 2023)
Food irradiation consists of a physical process that subjects food to doses of ionizing radiation, which are high enough energy to eliminate or neutralize harmful microbial contaminants without changing the taste or texture of food and without leaving residues. With this irradiation process we can prevent diseases transmitted by food, such as Salmonella and Escherichia coli, prolong the shelf life of foods, control pests that harm fruits by delaying germination and ripening, and finally sterilization, which allows their storage for years without refrigeration. The use of ionizing radiation for food preservation has been studied for several decades and is regulated in the USA by the Food and Drug Administration –FDA. In 1997, the World Health Organization - WHO released the use of the technique for all types of food. In Brazil, the first studies on food irradiation were carried out by the Center for Nuclear Energy in Agriculture - Cena, in the 50's. Currently, Brazilian legislation follows the international recommendations suggested by the Food and Agriculture Organization - FAO, the International Atomic Energy Agency - IAEA and Codex Alimentarius. The scope of this work is a survey, analysis and evolution of national and international legislation related to ionizing irradiation practices in food. For the preparation of this research, bibliographical reviews were carried out, consultations in Brazilian and international legislation, Internet sites, and in the documentation of the Gamma Irradiation Laboratory of the Nuclear Technology Development Center - CDTN